Social Media Engagement: the Role of Social Media Content and Customer Motivations for Using Non-profit Organisations' Social Media Sites - Chiu, Szu-Wei (2016)
Customer engagement has been acknowledged as a potential means to fill the gap in relationship marketing in order to cultivate more intimate donor-organisation relationships that go beyond mere donation. An organisation’s social media presence, as the main platform for developing such engagement, is considered to support the interaction between donors and organisations. This paper explored the factors that drive donor engagement, as well as the relationship between key constructs in the donor engagement model (Bennett, 2013) in a social media context. In particular, this research focused on the effect of organisational Instagram content and customer motivations for using non-profit organisations’ Instagram pages. A web survey was conducted to understand the potential antecedents of social media engagement. The results support prior literature, finding that social media engagement can be driven by a higher perceived quality of social media content and customer motivations for using organisational social media sites. Furthermore, a higher level of social media engagement is posited to result in higher intention to undertake related donor behaviours, including giving, Word-of-Mouth and future support. Accordingly, non-profit marketing practitioners are suggested to create engagement strategies that go beyond traditional model of relationship marketing to trigger a higher level of social media engagement.